Konstruktionsgrammatische Zugänge zur (soziokognitiven) Diskurssemantik - Bach, Matthieu (Linguistik Online, 2022)
In this paper, I propose an extension of Busse’s cognitive discourse semantics through a usage-based construction grammatical approach. Following Lasch (2015a, 2015b, 2016), I will argue that (i) constructions are discursive per se, and (ii) some constructions can fulfil a textual or discursive function depending on their usage. The theoretical discussion shows that construction grammar is arguably an interesting and fruitful tool of a cognitive discourse semantics, which is empirically explained with examples.